Spectrophotometric Determination of Zirconium in Water Samples - Zhang, Xiao-Xia; Zhao, Yan; Wang, Shuai-Min; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2012)
According to the property that in 2.40 mol L-1 nitric acid medium Zr(IV) can form a 1:3 blue complex nature with DBC-arsenazo (DBC-ASA), a new spectrophotometric method for the determination of Zr(IV) was established. The maximum absorption wavelength of the complex is 560 nm, Zr(IV) and absorbance in the range of 0-1.20 μg mL-1 obeys Beer's law. The apparent molar absorptivity of the method is e560 nm = 4.56 × 104 L mol-1 cm-1 and detection limit is 0.22 μg mL-1. The method was used for the determination of zirconium in water samples. The relative standard deviation of 13 determination was 1.71-1.96 % and the recovery was 95.8-104.1 %.